Grazing effects on intraspecific trait variability vary with changing precipitation patterns in Mongolian rangelands - Lang, Birgit; Ahlborn, Julian; Oyunbileg, Munkhzuul; Geiger, Anna; Wehrden, Henrik; Wesche, Karsten; Oyuntsetseg, Batlai; Römermann, Christine (Ecology and evolution, 2020)
Functional traits are proxies for plant physiology and performance, which do not only differ between species but also within species. In this work, we hypothesized that (a) with increasing precipitation, the percentage of focal species which significantly respond to changes in grazing intensity increases, while under dry conditions, climate‐induced stress is so high that plant species hardly respond to any changes in grazing intensity and that (b) the magnitude with which species change their trait values in response to grazing, reflected by coefficients of variation (CVs), increases with increasing precipitation. Chosen plant traits were canopy height, plant width, specific leaf area (SLA), chlorophyll fluorescence, performance index, stomatal pore area index (SPI), and individual aboveground biomass of 15 species along a precipitation gradient with different grazing intensities in Mongolian rangelands. We used linear models for each trait to assess whether the percentage of species that respond to grazing changes along the precipitation gradient. To test the second hypothesis, we assessed the magnitude of intraspecific trait variability (ITV) response to grazing, per species, trait, and precipitation level by calculating CVs across the different grazing intensities. ITV was most prominent for SLA and SPI under highest precipitation, confirming our first hypothesis. Accordingly, CVs of canopy height, SPI, and SLA increased with increasing precipitation, partly confirming our second hypothesis. CVs of the species over all traits increased with increasing precipitation only for three species. This study shows that it remains challenging to predict how plant performance will shift under changing environmental conditions based on their traits alone. In this context, the implications for the use of community‐weighted mean trait values are discussed, as not only species abundances change in response to changing environmental conditions, but also values of traits considerably change. Including this aspect in further studies will improve our understanding of processes acting within and among communities. We focused on the intraspecific changes of plant traits along a precipitation gradient with changing grazing pressure. In detail, we analyzed the intraspecific trait variability of seven traits (canopy height, plant width, specific leaf area, chlorophyll fluorescence, performance index, stomatal pore area index, and individual aboveground biomass) of 15 common steppe species along a precipitation gradient with different grazing intensities at each precipitation level in Mongolian rangelands. Our results highlight that both species and traits show specific or even opposite variability responses to the precipitation gradient under increasing grazing intensity.